2005
DOI: 10.1021/ma051270a
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Shifting Cationic Polymers That Promote Self-Assembly and Self-Disassembly with DNA

Abstract: Synthetic materials that assemble reversibly with polyanions under physiological conditions are of interest for a broad range of biotechnical applications. Cationic polymers are used widely as agents for the condensation of DNA, but polycations also introduce practical limitations in applications for which subsequent dissociation or disassembly of polycation/DNA complexes is desired. The design of cationic polymers that promote the release of associated DNA presents a challenge because it requires the introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
77
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 49 publications
2
77
0
1
Order By: Relevance
“…[21][22][23] The approach reported here is based not upon the use of degradable cationic polymers, but on the fabrication of multilayers using a new class of ester-functionalized, 'charge-shifting' polyamines. We [24,25] and others [26][27][28][29][30] have demonstrated that it is possible to disrupt ionic interactions in polyelectrolyte assemblies in physiologically relevant media using cationic polymers designed to undergo gradual reductions in net charge upon exposure to aqueous media. In general, approaches to the design of these 'charge-shifting' polymers have taken one of two basic routes: (i) the attachment of amine-functional side chains to polymer backbones through cleavable linkages, [25][26][27][28][29][30] or (ii) the conjugate addition of ester-functionalized 'charge-shifting' side chains to the backbones of cationic polymers.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[21][22][23] The approach reported here is based not upon the use of degradable cationic polymers, but on the fabrication of multilayers using a new class of ester-functionalized, 'charge-shifting' polyamines. We [24,25] and others [26][27][28][29][30] have demonstrated that it is possible to disrupt ionic interactions in polyelectrolyte assemblies in physiologically relevant media using cationic polymers designed to undergo gradual reductions in net charge upon exposure to aqueous media. In general, approaches to the design of these 'charge-shifting' polymers have taken one of two basic routes: (i) the attachment of amine-functional side chains to polymer backbones through cleavable linkages, [25][26][27][28][29][30] or (ii) the conjugate addition of ester-functionalized 'charge-shifting' side chains to the backbones of cationic polymers.…”
mentioning
confidence: 99%
“…In general, approaches to the design of these 'charge-shifting' polymers have taken one of two basic routes: (i) the attachment of amine-functional side chains to polymer backbones through cleavable linkages, [25][26][27][28][29][30] or (ii) the conjugate addition of ester-functionalized 'charge-shifting' side chains to the backbones of cationic polymers. [24] Polymer 1 is exemplary of this second design approach; gradual reductions in the net charge of this polymer can be made to occur upon hydrolysis of ester-functionalized side chains and the introduction of anionic charge (Eq 1; full protonation of amine functionality shown for illustrative purposes). [24] We demonstrated recently that this polymer can promote both self-assembly and timedependent disassembly with DNA in solution in ways that could be understood in terms of side chain hydrolysis and subsequent changes in the net charges of the polymer.…”
mentioning
confidence: 99%
See 3 more Smart Citations